Endoplasmic reticulum stress, autophagic and apoptotic cell death, and immune activation by a natural triterpenoid in human prostate cancer cells. Issue 4 (30th October 2018) - Johnson, Benjamin M.; Radwan, Faisal F. Y.; Hossain, Azim; Doonan, Bently P.; Hathaway‐Schrader, Jessica D.; God, Jason M.; Voelkel‐Johnson, Christina V.; Banik, Narendra L.; Reddy, Sakamuri V.; Haque, Azizul
Abstract: Though the current therapies are effective at clearing an early stage prostate cancer, they often fail to treat late‐stage metastatic disease. We aimed to investigate the molecular mechanisms underlying the anticancer effects of a natural triterpenoid, ganoderic acid DM (GA‐DM), on two human prostate cancer cell lines: the androgen‐independent prostate carcinoma (PC‐3), and androgen‐sensitive prostate adenocarcinoma (LNCaP). Cell viability assay showed that GA‐DM was relatively more toxic to LNCaP cells than to PC‐3 cells (IC50 s ranged 45‐55 µM for PC‐3, and 20‐25 µM for LNCaP), which may have occurred due to differential expression of p53. Hoechst DNA staining confirmed detectable nuclear fragmentation in both cell lines irrespective of the p53 status. GA‐DM treatment decreased Bcl‐2 proteins while it upregulated apoptotic Bax and autophagic Beclin‐1, Atg5, and LC‐3 molecules, and caused an induction of both early and late events of apoptotic cell death. Biochemical analyses of GA‐DM‐treated prostate cancer cells demonstrated that caspase‐3 cleavage was notable in GA‐DM‐treated PC‐3 cells. Interestingly, GA‐DM treatment altered cell cycle progression in the S phase with a significant growth arrest in the G2 checkpoint and enhanced CD4 + T cell recognition of prostate tumor cells. Mechanistic study of GA‐DM‐treated prostate cancer cells further demonstrated that calpain activation and endoplasmic reticulum stress contributed to cell death. These findings suggest that GA‐DM is a candidate for future drug design for prostate cancer as it activates multiple pathways of cell death and immune recognition. Abstract : Ganoderic acid DM (GA‐DM) regulates calpain via induction of endoplasmic reticulum stress in prostate cancer cells. GA‐DM modulates cell cycle progression in the S phase with an induction of growth arrest at the G2 checkpoint in prostate cancer cells. GA‐DM–induced autophagic and apoptotic cell death and promoted functional antigen presentation by prostate cancer cells.